Robot-Assisted, Laparoscopic, and Open Radical Cystectomy: Pre-Operative Data of 1400 Patients From The Italian Radical Cystectomy Registry - Busetto, Gian Maria; D’Agostino, Daniele; Colicchia, Michele; Palmer, Katie; Artibani, Walter; Antonelli, Alessandro; Bianchi, Lorenzo; Bocciardi, Aldo; Brunocilla, Eugenio; Carini, Marco; Carrieri, Giuseppe; Cormio, Luigi; et al. (Frontiers in Oncology, 2022)
Introduction: the Italian Radical Cystectomy Registry (RIC) is an observational prospective study aiming to understand clinical variables and patient characteristics associated with short- and long-term outcomes among bladder cancer (BC) patients undergoing radical cystectomy (RC). Moreover, it compares the effectiveness of three RC techniques - open, robotic, and laparoscopic. Methods: from 2017 to 2020, 1400 patients were enrolled at one of the 28 centers across Italy. Patient characteristics, as well as preoperative, postoperative, and follow-up (3, 6, 12, and 24 months) clinical variables and outcomes were collected. Results: preoperatively, it was found that patients undergoing robotic procedures were younger (p<.001) and more likely to have undergone preoperative neoadjuvant chemotherapy (p<.001) and BCG instillation (p<.001). Hypertension was the most common comorbidity among all patients (55%), and overall, patients undergoing open and laparoscopic RC had a higher Charlson Comorbidities Index (CCI) compared to robotic RC (p<.001). Finally, laparoscopic patients had a lower G-stage classification (p=.003) and open patients had a higher ASA score (p<.001). Conclusion: the present study summarizes the characteristic of patients included in the RIC. Future results will provide invaluable information about outcomes among BC patients undergoing RC. This will inform physicians about the best techniques and course of care based on patient clinical factors and characteristics.